HARMONI SOSIAL ANTARMAHASISWA MELALUI IMPLEMENTASI BILINGUAL PROGRAM DALAM PERKULIAHAN MATEMATIKA - Upu, Hamzah Upu; Jafar, Muh. Basri; Salam, Salam Salam (Indonesian Journal of Educational Studies, 2010)
Abstract. Inter-Students Social Harmony through Bilingual Program Implementation of Math Course. This study aims at developing (1) student textbook, (2) student worksheets, and (3) instructional plans written in English and taught bilingually. The long term goal is the establishment of cooperation and social harmonization among the students. This employs research and development (R & D) method. The results of the data analysis show (1) the way to build social harmony among the students while helping them understand mathematics is bilingual-based instruction, (2) the factors affecting the implementation of the bilingual program is native language, social interaction under the local/ethnicity viscosity, and basic math skills of students as background knowledge to understanding of the instruction. Â  Abstrak. Harmoni Sosial Antarmahasiswa Melalui Implementasi Bilingual Program dalam Perkuliahan Matematika. Penelitian ini berfokus untuk menghasilkan (1) buku ajar mahasiswa, (2) lembar kerja mahasiswa, dan (3) rencana pelaksanaan perkuliahan yang ditulis dalam bahasa Inggris dan diajarkan dengan bilingual. Tujuan jangka panjang adalah terjalinnya hubungan kerja sama dan harmonisasi sosial antarmahasiswa. Metode yang digunakan adalah Research and Development (R&D). Hasil analisis data menunjukkan (1) cara membangun harmoni sosial antarmahasiswa sekaligus membantu pemahaman matematika adalah perangkat pembelajaran berbasis Bilingual Program, (2) faktor yang memengaruhi implementasi Bilingual Program adalah bahasa ibu, interaksi sosial dengan nilai kekentalan daerah/etnis, dan kemampuan dasar matematika mahasiswa yang menjadi bekal awal dalam memahami perangkat pembelajaran. Â  Kata kunci: harmoni sosial, pembelajaran matematika, program bilingual Â